Changing gender norms around female genital mutilation/cutting (FGM/C): a key role for social work in the Global North - Villani, Michela (Frontiers in Sociology, 2023)
“Female genital mutilation/cutting” (FGM/C) refers to procedures that involve altering the external female genitalia with the aim of reinforcing gendered body norms. The literature has consistently shown that, like various forms of discrimination, the practice is rooted in systems of gender inequality. As a result, FGM/C has increasingly come to be understood in terms of social norms that are by no means fixed. And yet, in the Global North, interventions remain primarily medical in nature, with clitoral reconstruction having emerged as a common means of dealing with related sexual issues. And although treatments can vary greatly depending on the hospitals and physicians involved, sexuality tends to be considered from a gynecological perspective, even when multidisciplinary care is offered. By contrast, gender norms and other socio-cultural factors receive little attention. In addition to highlighting three critical shortcomings in current responses to FGM/C, this literature review also describes how social work can play a key role in overcoming the associated barriers by (1) adopting a holistic approach to sex education, one capable of addressing those aspects of sexuality that lie beyond the scope of a medical consultation; (2) supporting family-based discussions on matters of sexuality; and (3) promoting gender equality, especially among younger generations.